A Fatal Case of Descending Necrotizing Mediastinitis as a Result of Treatment Delay in Odontogenic Infection: Various Bacterial Infections and Coexisting Lung Tuberculosis - Husen, Theresia Feline; Sari, Grace Natalia; Gunawan, Putri Amadea; Vidya, Ananda Pipphali; Wardoyo, Suprayitno (Jurnal Respirasi, 2025)
Introduction: Descending necrotizing mediastinitis (DNM) is a rare but life-threatening complication of oropharyngeal and odontogenic infections. This case report highlighted that DNM is very complex because it causes infection with various types of bacteria, and the presence of pulmonary tuberculosis (TB) in the patient. Case: A patient with untreated pulp gangrene for three months underwent drainage and tooth extraction surgery. Subsequently, the patient was diagnosed with DNM and underwent cervicotomy and sternotomy for debridement. Postoperative cultures revealed polymicrobial infections. Additionally, a follow-up chest X-ray confirmed active pulmonary TB. The simultaneous presence of multiple bacterial infections and TB necessitated aggressive treatment, including broad-spectrum antibiotics, anti-TB drugs per standard regimens, and close intensive care unit (ICU) monitoring. Over a month of ICU care, the patient’s vital signs and postoperative wounds improved. This case was classified as Endo-Hasegawa IIC DNM caused by odontogenic infection with pulp gangrene, progressing from the submandibular space to the mediastinum. The coexisting pulmonary TB further complicated management. Drainage via cervicotomy and sternotomy allowed for extensive mediastinal exploration. However, delayed diagnosis led to complications, including sepsis and altered consciousness due to uncontrolled bacterial spread. This underscores the importance of early diagnosis and intensive, multidisciplinary management to improve outcomes. Conclusion: Physicians need to be more aware of DNM as a potential complication of odontogenic infections and the possibility of a wide variety of bacterial and coexisting infections that may complicate treatment.